Analysis of Public Knowledge, Attitudes, and Practices in Food and Drug Selection in Indonesia - Wikara, Tina; Astuti, Sri; Nurhayati, Sri; Carolina, Rotua Uli; Sari, Evi Ratna (Kesmas, 2025)
As consumers, the public plays a vital role in ensuring the safe and appropriate use of products. This study aimed to assess awareness of food and drug safety and quality among the Indonesian population. Using a cross-sectional survey, the authors measured public awareness across three key dimensions: knowledge, attitudes, and practices. Data were collected from 20,610 respondents aged 17–65 years from 34 provinces in Indonesia. The survey approach employed a three-stage stratified sampling design. Data were collected through structured face-to-face interviews, and the results were presented as an index ranging from 0 to 100 (low to high awareness). The respondents demonstrated good knowledge (92.85), attitudes (90.46), and practices (80.97). The average overall Awareness Index was 88.09. The authors observed significant variations by region, age, education, and occupation, but not by sex. The gap between knowledge and attitudes, and practices can be regarded as a public health concern. Awareness of food and drug safety and quality that does not manifest in behavioral practices does not protect consumers from harm.